The young Oxford book of astronomy - Mitton, Simon, 1946-; Mitton, Jacqueline (New York, N.Y. : Oxford University Press, 1995)
Introduction to planets, stars, galaxies, and the universe, featuring photographs and illustrations, and discussing the new technologies astronomers use when exploring space.
Includes index.
Books for the Teen Age (NYPL).
Wilson's Children.
Wilson's Junior High School.
6.0.
6.0
Keywords: Astronomy -- Juvenile literature; Astronomy; Astronomy